Method for improving direct reduction performance of ultrafine iron ore concentrate pellets
Patent Information
- Application Number
- CN202611172598.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-13
AI Technical Summary
超细铁精矿虽有利于提高球团矿的铁品位和抗压强度,但其比表面积大、颗粒堆积致密,导致预热焙烧过程中球团内部孔隙率显著降低,晶粒间固相扩散充分进行,形成高度致密的显微结构
本发明在保持球团矿高品位(TFe≥65.5%)和高抗压强度(≥2800N/个球)的前提下,通过褐铁矿添加、石灰石特定粒度调控及碱度优化,有效提升了超细铁精矿球团的最终还原度(R90≥92%)和金属化率(≥88%),并同步实现了低温还原粉化率(≤3%)和聚集指数(<16)的优良控制,解决了超细磁铁矿球团因结构致密导致还原性差的技术难题,为直接还原竖炉提供了兼具高强度、高品位、高还原性、低粉化和抗黏结的优质炉料。
Smart Images

Figure CN122898731A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of iron and steel metallurgy, and particularly relates to a method for improving the direct reduction performance of ultrafine iron concentrate pellets. Background Technology
[0002] Direct reduced iron (DRI) is an ideal raw material for electric arc furnace (EAF) smelting of high-quality special steels, boasting significant advantages such as low levels of harmful elements, uniform quality, and hot charging and delivery. With the steel industry's development towards high-end, intelligent, and green technologies, and the continued growth in demand for high-strength steel and special alloys, the proportion of short-process EAF steelmaking is gradually increasing, leading to rapid growth in the market demand for DRI. However, the traditional gas-based vertical shaft furnace direct reduction (DRI) process places stringent requirements on the reduction performance of iron pellets. The degree of reduction, metallization rate, and low-temperature reduction pulverization performance of the pellets directly determine the output indicators and energy consumption levels of the DRI production line. Furthermore, the agglomeration and pulverization problems of the pellets during the reduction process are key bottlenecks restricting the stable and smooth operation of the vertical shaft furnace.
[0003] Direct reduced iron (DRI) is an ideal raw material for electric arc furnace (EAF) smelting of high-quality special steels, boasting significant advantages such as low levels of harmful elements, uniform quality, and hot charging and delivery. With the steel industry's development towards high-end, intelligent, and green technologies, and the continued growth in demand for high-strength steel and special alloys, the proportion of short-process EAF steelmaking is gradually increasing, leading to rapid growth in the market demand for DRI. However, the traditional gas-based vertical shaft furnace direct reduction (DRI) process places stringent requirements on the reduction performance of iron pellets. The degree of reduction, metallization rate, and low-temperature reduction pulverization performance of the pellets directly determine the output indicators and energy consumption levels of the DRI production line. Furthermore, the agglomeration and pulverization problems of the pellets during the reduction process are key bottlenecks restricting the stable and smooth operation of the vertical shaft furnace.
[0004] Currently, high-grade acidic iron ore pellets are the mainstream product for direct reduction (DRI). To meet the iron grade requirements of DRI products, the raw materials for pellets are gradually shifting towards ultrafine-grained high-grade magnetite concentrate. After fine grinding and magnetic separation, this type of iron concentrate can achieve 100% -200 mesh content and over 90% -325 mesh content. While ultrafine iron concentrate is beneficial for improving the iron grade and compressive strength of pellets, its large specific surface area and dense particle packing lead to a significant reduction in internal porosity during preheating and roasting, resulting in sufficient solid-phase diffusion between grains and the formation of a highly dense microstructure. This structural feature poses a dual constraint on the subsequent gas-based direct reduction process: on the one hand, the dense structure significantly increases the mass transfer resistance of reducing gases (CO, H2) diffusing inward, reducing the effective area of the reaction interface, resulting in a lower reduction rate and reduced degree of reduction in the pellets; on the other hand, the formation of low-melting-point phases such as Fe2SiO4 is intensified during the reduction process, which easily induces agglomeration and sticking between pellets in the high-temperature reduction zone of the vertical shaft furnace, which can lead to suspension of material and shutdown of the vertical shaft furnace in severe cases, becoming a problem that restricts the large-scale and stable operation of the direct reduction process.
[0005] To improve the reduction performance of pellets, existing process technology improvement paths include: (1) adjusting roasting process parameters (reducing roasting temperature and shortening roasting time) in order to retain more pores in the pellets. However, this measure often leads to insufficient compressive strength of the pellets (<2500N / pellet), which is difficult to meet the strength requirements of the vertical furnace for the pellets entering the furnace; (2) adding pore-forming agents (such as sawdust, starch, carbonates, etc.) to increase porosity by decomposing and releasing gases during roasting. However, if the amount of pore-forming agent added is not properly controlled, it can easily lead to a significant deterioration in the strength of the pellets, and the residual combustion products of some pore-forming agents can affect the high-temperature metallurgical performance of the pellets; (3) adjusting the basicity of the pellets and adding limestone or dolomite to acidic pellets to prepare flux pellets. By generating low-melting-point binder phases such as calcium ferrite, solidification can be achieved at a lower temperature to retain more pores. However, the CO2 generated by the decomposition of limestone creates pressure inside the pellets. If the particle size is too fine, the decomposition is too fast and the pore distribution is uneven. If the particle size is too coarse, the decomposition is insufficient and the sintering effect is poor. In addition, as a low-grade iron ore, limonite has the characteristic of forming a large number of micropores during the decomposition of crystal water during pellet roasting. In recent years, researchers have tried to use it to improve the reducibility of pellets. However, due to the low iron grade of limonite itself (usually TFe < 60%) and the high content of gangue such as SiO2 and Al2O3, excessive addition will lead to a significant decrease in the iron grade of the pellets, making it difficult to meet the industry threshold requirement of TFe > 65% for pellets used in direct reduction. Moreover, the increase in gangue components exacerbates the risk of low-melting-point phase formation, which has an uncertain impact on the bonding behavior during the reduction process.
[0006] Therefore, it is necessary to develop a solution that takes into account the comprehensive indicators of high grade, high strength, high reducibility and anti-caking properties to improve the direct reduction performance of ultrafine iron concentrate pellets, thereby enhancing the porosity and reducibility of the pellets. Summary of the Invention
[0007] To overcome the shortcomings of the existing technology, the purpose of this invention is to provide a method to improve the direct reduction performance of ultrafine iron concentrate pellets. By adding limonite and adjusting the alkalinity with limestone and dolomite, the method significantly improves the reducibility and metallization rate of the pellets while ensuring high grade and high strength, and improves the low-temperature reduction pulverization and anti-caking properties, thus meeting the comprehensive requirements of direct reduction shaft furnaces for high-quality furnace feed.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for improving the direct reduction performance of ultrafine iron concentrate pellets includes the following steps: 1) Raw materials: ultrafine high-grade magnetite, limonite powder (MAC), limestone, dolomite, bentonite; The limonite powder is finely ground to a particle size of -200 mesh with a mass fraction ≥85 wt%. The limestone particle size distribution satisfies the following: the mass fraction of particles > 150 mesh is 14.0 wt% to 22.0 wt%, the mass fraction of particles 150 to 200 mesh is 14.5 wt% to 23.0 wt%, and the mass fraction of particles < 200 mesh is 55.0 wt% to 71.0 wt%.
[0009] The dolomite mentioned is finely ground to -200 mesh, accounting for more than 90 wt%; The ultrafine high-grade magnetite contains 100 wt% of -200 mesh and 90 wt% or more of -325 mesh; The bentonite-200 mesh content is above 95 wt%.
[0010] 2) Ingredients are mixed and formed into balls: Weigh each raw material according to the following weight percentages: The raw materials are made of 85%~93% ultrafine high-grade magnetite, 8%~12% MAC of limonite powder, and 0.7%~1.2% bentonite, with limestone and dolomite added to adjust the basicity of the pellets (CaO / SiO2) to 0.8~1.0. The weighed raw materials are mixed with water and then fed into a disc pelletizer to produce green pellets. 3) Preheating and roasting: After drying the green pellets, they are preheated at 900~950℃ for 6~10 minutes to obtain preheated pellets. The preheated pellets are then roasted at 1240~1260℃ for 8~12 minutes to obtain ore pellets.
[0011] Furthermore, in step 3), the preheating is carried out in a horizontal tubular furnace.
[0012] Furthermore, the total iron content (TFe) of the limonite powder MAC mentioned in step 1) is 59%~61%, and the loss on ignition is 7.0%~7.5%.
[0013] Furthermore, the dolomite described in step 1) is finely ground to a particle size of -200 mesh, accounting for 100%.
[0014] Further, the amount of water added in step 2) is 9.0wt%~10.0wt%.
[0015] Furthermore, the drop strength of the green balls obtained in step 2) is ≥5.0 drops / ball, and the compressive strength of the green balls is ≥10.0N / ball.
[0016] Further, the drying described in step 3) is drying in an oven at 100~108°C until constant weight.
[0017] Furthermore, the compressive strength of the preheated balls obtained in step 3) is ≥500N / ball.
[0018] Furthermore, the compressive strength of the pellets obtained in step 3) is ≥2800N / pellet, and the total iron content (TFe) is ≥65.5%.
[0019] Compared with the prior art, the beneficial effects of the present invention are: This invention, while maintaining high grade (TFe≥65.5%) and high compressive strength (≥2800N / pellet) of the pellets, effectively improves the final reducibility (R90≥92%) and metallization rate (≥88%) of ultrafine iron concentrate pellets by adding limonite, controlling specific particle size of limestone, and optimizing alkalinity. It also achieves excellent control of low-temperature reduction pulverization rate (≤3%) and aggregation index (<16), solving the technical problem of poor reducibility of ultrafine magnetite pellets due to their dense structure. This invention provides a high-quality furnace charge with high strength, high grade, high reducibility, low pulverization, and anti-caking properties for direct reduction shaft furnaces.
[0020] The green pellets prepared by this invention require a small amount of bentonite. Under the condition that the bentonite addition is only 0.7%~1.2%, the resulting green pellets have a drop strength of ≥5.0 times / pellet and a compressive strength of ≥10.0 N / pellet. This indicates that the mixture of ultrafine magnetite with limonite, limestone and dolomite has good pelletizing properties and sufficient green pellet strength, which meets the requirements for furnace feeding in the subsequent preheating and roasting process.
[0021] The present invention preheats the pellets to a strength of 500N / pellet. The use of a lower preheating temperature and a shorter preheating time helps to reduce energy consumption and avoids premature densification of the pellets during the preheating process, thus laying the foundation for retaining a suitable pore structure in the subsequent calcination stage. Attached Figure Description
[0022] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation
[0023] The present invention will now be described in detail with reference to the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0024] Example 1:
[0025] The main chemical components and physical properties of the raw materials are shown in Tables 1-3.
[0026] Table 1: Results of Chemical Composition Testing of Raw Materials
[0027] The limonite used is from the MAC mining area in Australia, with a crystallization water decomposition temperature of 300℃~450℃. The bentonite selected is composite bentonite, manufactured by China Construction Energy & Wisdom Non-metallic Materials (Liaoning) Co., Ltd.
[0028] Table 2: Detection Results of Particle Size Composition of Iron Concentrate and Limestone Raw Materials
[0029] Table 3: Particle size composition of limestone after particle size increase
[0030] At an alkalinity of 0.8, 85.21% magnetite, 9.47% finely ground limonite, 1.63% limestone, 2.46% dolomite, and 1.23% bentonite were blended and pelletized (water was added until the green pellet moisture content was 7.5%~8.5%, the pelletizing time of the disc pelletizer was approximately 10 minutes, the disc inclination angle was 44°, and the rotation speed was 22 r / min). The resulting green pellets had a drop rate of 5.1 times per pellet and a compressive strength of 11.0 N per pellet. After drying (drying in an oven at 105℃ to constant weight), the green pellets were preheated and calcined in a horizontal tube furnace at 900℃ for 8 minutes to obtain preheated pellets with a strength of 503 N per pellet. The preheated pellets were then calcined at 1250℃ for 10 minutes to obtain calcined pellets with a compressive strength of 2993 N per pellet. The above test results are all average values obtained from measurements of at least 20 pellets. The main chemical composition of the final pellets is shown in Table 4.
[0031] Table 4: Main Chemical Components of 0.8 Alkalinity Pelletize
[0032] The direct reduction performance of the pellets was tested in accordance with the standard ISO11258:2007 / GB / T24236-2009 "Determination of reduction index, final reduction degree and metallization of iron ore for direct reduction furnace". The test results of its reduction performance are shown in Table 5.
[0033] Table 5: Direct Reducibility of 0.8 Alkalinity Pellet
[0034] The standard used for testing was (ISO11257:2007IDT) "Determination of pulverization and metallization of iron ore for direct reduction furnace charge by gas-based direct reduction method". The test results are shown in Table 6.
[0035] Table 6: Direct Reduction Low-Temperature Differentiation Rate of 0.8 Alkalinity Pellet
[0036] The results of the reduction degree test of the 0.8 alkalinity pellets show that both types of pellets have high final reduction degree and metallization rate, and good reduction index.
[0037] The results of the low-temperature reduction pulverization rate and metallization rate tests of the pellets show that the two types of pellets have good low-temperature reduction pulverization performance.
[0038] According to the standard "Determination of Agglomeration Properties of Iron Ore Pellets for Direct Reduction Furnaces" (ISO 11256-2006), the aggregation index of iron ore pellets was determined by direct reduction method under specified test conditions. The aggregation index of the pellets was 14.81, which is considered good.
[0039] Example 2:
[0040] The main chemical components and physical properties of the raw materials are shown in Tables 1-3.
[0041] At an alkalinity of 0.88, 88.06% magnetite, 6.63% finely ground limonite, 1.69% limestone, 2.46% dolomite, and 1.16% bentonite were blended and pelletized (water was added until the green pellet moisture content was 7.8%–8.2%, the pelletizing time on a disc pelletizer was 10 ± 2 min, the disc inclination angle was 44°, and the rotation speed was 22 r / min). The resulting green pellets had a drop rate of 5.0 times per pellet and a compressive strength of 12.0 N per pellet. After drying (in an oven at 105℃ to constant weight), the green pellets were preheated and roasted in a horizontal tube furnace at 900℃ for 8 min to obtain preheated pellets. The preheated pellets were then roasted at 1250℃ for 10 min to obtain roasted pellets with a compressive strength of 3008 N per pellet. The main chemical composition of the final pellets is shown in Table 7.
[0042] Table 7: Main Chemical Components of 0.88 Alkalinity Pellet
[0043] The direct reduction performance of the pellets was tested in accordance with the standard ISO11258:2007 / GB / T24236-2009 "Determination of reduction index, final reduction degree and metallization of iron ore for direct reduction furnace". The test results of its reduction performance are shown in Table 8.
[0044] Table 8: Direct Reducibility of Pelletite with Alkalinity of 0.88
[0045] The standard used for testing was (ISO11257:2007IDT) "Determination of pulverization and metallization of iron ore for direct reduction furnace charge by gas-based direct reduction method". The test results are shown in Table 9.
[0046] Table 9: Direct Reduction Low-Temperature Differentiation Rate of 0.8 Alkalinity Pellet
[0047] The NOB pellet reduction test results show that both types of pellets have high final reduction and metallization rates, indicating good reduction performance.
[0048] The results of the low-temperature reduction pulverization rate and metallization rate tests of the pellets show that the two types of pellets have good low-temperature reduction pulverization performance.
[0049] According to the standard "Determination of Agglomeration of Iron Ore Pellets for Direct Reduction Furnace Charges" (ISO 11256-2006), the aggregation index of iron ore pellets was determined by direct reduction method under specified test conditions.
[0050] The aggregation index of the pellets was 15.64, which is relatively good.
[0051] Example 3:
[0052] The main chemical components and physical properties of the raw materials are shown in Tables 1-3.
[0053] At an alkalinity of 0.95, a mixture of 90.87% magnetite, 3.79% finely ground limonite, 1.73% limestone, 2.46% dolomite, and 1.16% bentonite was used for pelletizing (water was added until the green pellet moisture content was 8.0%–8.2%, pelletizing time on a disc pelletizer was 11 ± 1 min, disc inclination angle was 44°, and rotation speed was 22 r / min). The resulting green pellets had a drop rate of 5.3 times per pellet and a compressive strength of 11.3 N per pellet. After drying (in an oven at 105℃ to constant weight), the green pellets were preheated and roasted in a horizontal tube furnace at 900℃ for 8 min to obtain preheated pellets. The preheated pellets were then roasted at 1250℃ for 10 min to obtain roasted pellets with a compressive strength of 2941 N per pellet. The main chemical composition of the final pellets is shown in Table 10.
[0054] Table 10: Main Chemical Components of 0.8 Alkalinity Pelletize
[0055] The direct reduction performance of the pellets was tested in accordance with the standard ISO11258:2007 / GB / T24236-2009 "Determination of reduction index, final reduction degree and metallization of iron ore for direct reduction furnace". The test results of its reduction performance are shown in Table 11.
[0056] Table 11: Direct Reducibility of Pelletite with Alkalinity of 0.8
[0057] The standard used for testing was (ISO11257:2007IDT) "Determination of pulverization and metallization of iron ore for direct reduction furnace charge by gas-based direct reduction method". The test results are shown in Table 12.
[0058] Table 12: Direct Reduction Low-Temperature Differentiation Rate of 0.8 Alkalinity Pellet
[0059] The NOB pellet reduction test results show that both types of pellets have high final reduction and metallization rates, indicating good reduction performance.
[0060] The results of the low-temperature reduction pulverization rate and metallization rate tests of the pellets show that the two types of pellets have good low-temperature reduction pulverization performance.
[0061] According to the standard "Determination of Agglomeration of Iron Ore Pellets for Direct Reduction Furnace Charges" (ISO 11256-2006), the aggregation index of iron ore pellets was determined by direct reduction method under specified test conditions.
[0062] The aggregation index of the pellets was 14.88, which is relatively good.
[0063] Example 4:
[0064] The main chemical components and physical properties of the raw materials are shown in Tables 1-3.
[0065] At an alkalinity of 1.0, ore was blended and pelletized from 92.74% magnetite, 1.89% finely ground limonite, 1.75% limestone, 2.46% dolomite, and 1.10% bentonite. The resulting green pellets had a drop rate of 5.1 times per pellet and a compressive strength of 12.2 N per pellet. After drying, the green pellets were preheated and roasted in a horizontal tube furnace at 900℃ for 8 minutes to obtain preheated pellets. These preheated pellets were then roasted at 1250℃ for 10 minutes to obtain roasted pellets with a compressive strength of 2919 N per pellet. The main chemical composition of the final pellets is shown in Table 13.
[0066] Table 13: Main Chemical Components of 1.0 Alkalinity Pelletize
[0067] The direct reduction performance of the pellets was tested in accordance with the standard ISO11258:2007 / GB / T24236-2009 "Determination of reduction index, final reduction degree and metallization of iron ore for direct reduction furnace". The test results of its reduction performance are shown in Table 14.
[0068] Table 14: Direct Reducibility of 0.8 Alkalinity Pellet
[0069] The standard used for testing was (ISO11257:2007IDT) "Determination of pulverization and metallization of iron ore for direct reduction furnace charge by gas-based direct reduction method". The test results are shown in Table 15.
[0070] Table 15: Direct Reduction Low-Temperature Differentiation Rate of 0.8 Alkalinity Pellet
[0071] The NOB pellet reduction test results show that both types of pellets have high final reduction and metallization rates, indicating good reduction performance.
[0072] The results of the low-temperature reduction pulverization rate and metallization rate tests of the pellets show that the two types of pellets have good low-temperature reduction pulverization performance.
[0073] According to the standard "Determination of Agglomeration of Iron Ore Pellets for Direct Reduction Furnace Charges" (ISO 11256-2006), the aggregation index of iron ore pellets was determined by direct reduction method under specified test conditions.
[0074] The aggregation index of the pellets was 15.61, which is relatively good.
[0075] In addition, during the pelletizing stage, the amounts of limonite powder MAC, limestone, dolomite, and bentonite were adjusted within the raw material ratio range to keep the alkalinity at 0.8. Three groups of pellets with limonite ratios of 8.0%, 10.0%, and 12.0% were prepared respectively. The compressive strength (≥2800N / pellet), TFe (≥65.5%), and reducibility (R90≥92%) of the obtained pellets all met the requirements of high-quality furnace feed.
[0076] This invention, while maintaining the high grade and high compressive strength of the iron concentrate pellets, effectively improves the final reducibility and metallization rate of ultrafine iron concentrate pellets by adding limonite, controlling the specific particle size of limestone, and optimizing alkalinity. It also achieves excellent control over the low-temperature reduction pulverization rate and aggregation index, solving the technical problem of poor reducibility of ultrafine magnetite pellets due to their dense structure. This provides a high-quality furnace charge for direct reduction shaft furnaces that combines high strength, high grade, high reducibility, low pulverization, and anti-caking properties.
Claims
1. A method for improving the direct reduction performance of ultrafine iron concentrate pellets, characterized in that, Includes the following steps: 1) Raw materials: ultrafine high-grade magnetite, limonite powder (MAC), limestone, dolomite, bentonite; The limonite powder is finely ground to a particle size of -200 mesh with a mass fraction ≥85 wt%. The limestone particle size distribution satisfies the following: 14.0 wt% to 22.0 wt% for particles > 150 mesh, 14.5 wt% to 23.0 wt% for particles 150 to 200 mesh, and 55.0 wt% to 71.0 wt% for particles < 200 mesh. The dolomite mentioned is finely ground to -200 mesh, accounting for more than 90 wt%; The ultrafine high-grade magnetite contains 100 wt% of -200 mesh and 90 wt% or more of -325 mesh; The bentonite-200 mesh content is above 95 wt%; 2) Ingredients are mixed and formed into balls: Weigh each raw material according to the following weight percentages: The raw materials are made of 85%~93% ultrafine high-grade magnetite, 8%~12% MAC of limonite powder, and 0.7%~1.2% bentonite. Limestone and dolomite are added to adjust the basicity of the pellets (CaO / SiO2) to 0.8~1.
0. The weighed raw materials are mixed with water and then fed into a disc pelletizer to form green pellets. 3) Preheating and roasting: After drying the green pellets, they are preheated at 900~950℃ for 6~10 minutes to obtain preheated pellets. The preheated pellets are then roasted at 1240~1260℃ for 8~12 minutes to obtain ore pellets.
2. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, In step 3), the preheating is carried out in a horizontal tubular furnace.
3. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The total iron content (TFe) of the limonite powder MAC mentioned in step 1) is 59%~61%, and the loss on ignition is 7.0%~7.5%.
4. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The dolomite mentioned in step 1) is finely ground to a particle size of -200 mesh, accounting for 100%.
5. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The amount of water added in step 2) is 9.0wt%~10.0wt%.
6. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The drop strength of the green balls obtained in step 2) is ≥5.0 drops / ball, and the compressive strength of the green balls is ≥10.0N / ball.
7. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The drying described in step 3) is drying in an oven at 100~108℃ until constant weight.
8. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The compressive strength of the preheated balls obtained in step 3) is ≥500N / ball.
9. The method for improving the direct reduction performance of ultrafine iron concentrate pellets according to claim 1, characterized in that, The compressive strength of the pellets obtained in step 3) is ≥2800N / pellet, and the total iron content (TFe) is ≥65.5%.